PENGARUH PHYSICAL EVIDENCE TERHADAP KEPUTUSAN PEMILIHAN PROGRAM STUDI MANAJEMEN FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS AHMAD DAHLAN - Suryana Hendrawan (Universitas Ahmad Dahlan, 2021)
This study aims to analyze the factors influencing physical evidence on student decisions in choosing the Management Study Program, Faculty of Economics and Business, Universitas Ahmad Dahlan, either simultaneously or partially. This research is explanatory research with a quantitative approach. This study uses multiple analysis tests to find the partial and simultaneous effect between the dependent and independent variables. The validity and reliability used in this study have met the requirements. The results of this study indicate that facility exterior, facility interior, and other tangibles factors influencing the decision to choose the Management Study Program, Faculty of Economics and Business, Universitas Ahmad Dahlan. The result also shows that Physical Evidence Variables are simultaneously influencing the student's decision to choose the Management Study Program, Faculty of Economics and Business, Universitas Ahmad Dahlan.